MORALS OF VIETNAMESE STUDENT IN THE CONTEXT OF MARKET ECONOMY AND INTERNATIONAL INTEGRATION - Ly, Pham (IJRDO- Journal of Educational Research, 2018)
In the current socialist reform of Vietnam, the transformation of the centrally planned economy into a market economy model, the changing of religious values virtue is inevitable. The current market economy and international integration have been strongly influenced both in the positive and negative aspects of economic, political, cultural, ideological and moral aspects. One of the issues that has become the focus of attention is the change in perceptions of the values of a lot of students. This raises a number of pressing issues that need to be addressed in the new context.